Politics in the workplace : how can managers keep the peace? - Thompson, Lemaro (MIT Sloan Management Review, 2022)
When political discussions enter the workplace, partisan disagreements can lead to a range of issues, including stereotyping, bias, discrimination, and animosity among coworkers. But providing guidelines for civil political discourse is often not enough to prevent uncivil behavior. The author offers five recommendations to help managers avoid the damage to workplace relationships and culture that can result from ideological disagreements.